Eyes Outside a Boundary Line: An Example of the Willats Region-Drawing Theory?. (July 2020) - Carboni, Selene; Kennedy, John M.
A puzzling raised-line drawing of a head by a blind man with no experience in freehand drawing has eyes placed outside the boundary line of the head, not inside. After scribbling, in the John Willats theory of drawing development, 2D "regions" on the page stand for 3D "volumes" in the scene. If Willats is correct, in very early drawing development circles touching the boundary line from outside may show the eyes are "embedded, " and very early drawing development may be similar in the blind and sighted.